The Assistance to Develop Creativity in Early Childhood (TK) Using Plasticine Amid The Covid-19 Pandemic - Miftakhuljanah, Az Zahro; Sugiyanto, Sugiyanto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
During the Covid-19 pandemic, almost all schools carried out online learning, but children became bored and played more. It will be more dangerous if children play outside the home environment and hang out freely with their friends so that they have the potential to contract corona. UNS Covid-19 KKN has an alternative way of playing that is interesting and develops creativity, namely the play with plasticine program. This program is implemented in Kretek Village, Karang Sembung RT 03/04, Kebumen Regency. The participants consisted of 4 children, 1 kindergarten teacher and 1 parent. In the implementation, the children were divided into groups, but each child made his own work according to the theme. Children are able to form plasticine works with themes, including food, fruits, a zoo atmosphere, and so on. The results of this program show: 1) children's creativity can develop, 2) play activities outside the home environment are reduced, 3) learning according to health protocols, namely adjusting distance in interactions 4) experience exchange occurs 5) parents are motivated in learning to guide children learning while playing.